The Genesy Model for a Blockchain-Based Fair Ecosystem of Genomic Data - Carlini, Federico; Carlini, Roberto; Dalla Palma, Stefano; Pareschi, Remo; Zappone, Federico (Frontiers in Blockchain, 2020)
Recent advances in technology have drastically downsized costs and implementation times for genomic services. The wide availability of low-cost genomic technologies and easy access to genomic data can significantly improve the productivity and efficiency of healthcare, all to the benefit of social well-being in general. For example, by creating the conditions for researchers to identify the causes of multiple diseases and by contributing to the development of new drugs, we can improve the quality of life and give people, as users of genomic services, the means to positively impact their health. This article describes how blockchain technology can lay the foundations of an ecosystem that encourages users to acquire and share their genomic data in full awareness and without fear of being circumvented, so as to participate in the benefits and advances in genomic research. The starting point is Genesy, an innovative blockchain platform that transcribes genomic data, thus facilitating and at the same time safeguarding, the users of genomic services in their relationships with parties interested in accessing and using data they own, such as research centers, pharmaceutical companies, hospitals and geneticists. This result is obtained by exploiting the capabilities of blockchain technology to notarize data and prevent their unauthorized use, and at the same time to make them objects of possible transactions between different parties. Looking ahead, the Genesy model can be generalized to promote an ecosystem, and a fair market, for all types of biomedical data.